Silence : the currency of power - Achino-Loeb, Maria-Luisa (Berghahn, 2006)
This book is about silence and power and how they interact. It argues that only by studying how silence works-how it is implicated in the construction of meaning-can we arrive at the elusive roots of power in all its dimensions. Silence becomes the currency of power by delineating the margins or what we perceive and through a sleight of hand wherein behaviors undertaken in the service of self-interest appear instead as inevitable and devoid of human agency. The theoretical load of this argument is carried by vivid ethnographic material dealing with music, linguistic behavior, racial conflicts, work dislocations, and the construction of anthropological subjects and texts.